Genetic Architectures of Psychiatric Disorders: The Emerging Picture and Its Implications - Sullivan, Patrick F. (2012)
Psychiatric disorders are among the most intractable enigmas in medicine. In the past five years, there has been unprecedented progress on the genetics of many of these conditions. In this review, we discuss the genetics of nine cardinal psychiatric disorders (Alzheimer’s disease, attention-deficit hyperactivity disorder, alcohol dependence, anorexia nervosa, autism spectrum disorder, bipolar disorder, major depressive disorder, nicotine dependence, and schizophrenia). Empirical approaches have yielded new hypotheses about etiology, and now provide data on the often debated genetic architectures of these conditions, which have implications for future research strategies. Further study using a balanced portfolio of methods to assess multiple forms of genetic variation is likely to yield many additional new findings.